MODEL PENINGKATAN KINERJA SDM PADA DOMPET PEDULI UMMAT DAARUT TAUHID CABANG SEMARANG - Andri Adi (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2017)
HR performance improvement is an intended thing which is going to endure in order to achievethe perfect result continuously. Several factors to improve the performance of human resourcesin order to create maximum performance include competency-based human resourcedevelopment, achievement motivation, Islamic work ethic and HR performance itself. Thisresearch used the population at Lembaga Amil Zakat Nasional Dompet Peduli Ummat DaarutTauhiid Cabang Semarang period 2015. The number of sample was 30 respondents with usingthe sample by census i.e. that the sample taken was equal with the number of population. Basedon the analysis, the result can be concluded that there is no influence between competencybasedhuman resource development to the Human Resource Performances significantly,there is no influence between competency-based human resource development towardsachievement motivation significantly, and there is an influence between Islamic Work Ethictowards achievement motivation and there is an influence between achievement motivationtowards the Human Resource Performances significantly, while there is no influence betweenIslamic Work Ethic to the Human Resource Performances.Keywords : Competency-Based Human Resources Development, Achievement Motivation,Islamic Work Ethics and Human Resources Performance